"King of the zombies" - Yarbrough, Jean; Purcell, Dick, 1908-1944; Kelso, Edmond; Monogram Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Monogram Pictures Corporation, 1941)
During World War II, a small plane is blown off course by a storm. Guided by a faint radio signal, they crash on an island. The passenger, his manservant and the pilot take refuge in a mansion owned by a doctor. The easily-spooked manservant soon becomes convinced the mansion is haunted by zombies and ghosts. --
Originally released as a motion picture in 1941.
Dick Purcell, Joan Woodbury, Mantan Moreland.
Cinematographer, Mack Stengler; editor, Richard Currier; music
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Zombies -- Drama; Air pilots -- Drama; World War, 1939-1945 -- Drama; Islands -- Drama; Horror films; Feature films; Comedy films; Zombie films; Internet videos; Streaming video